KPC-3–Producing Serratia marcescens Outbreak between Acute and Long-Term Care Facilities, Florida, USA - Adriana Jimenez; Lilian M. Abbo; Octavio Martinez; Bhavarth Shukla; Kathleen Sposato; Alina Iovleva; Erin Louise Fowler; Christi Lee McElheny; Yohei Doi (Emerging Infectious Diseases, 2020)
We describe an outbreak caused by Serratia marcescens carrying blaKPC-3 that was sourced to a long-term care facility in Florida, USA. Whole-genome sequencing and plasmid profiling showed involvement of 3 clonal lineages of S. marcescens and 2 blaKPC-3-carrying plasmids. Determining the resistance mechanism is critical for timely implementation of infection control measures.